(untitled) (Journal of Production Engineering, 2022)
Five types of bevel gears having different shaft angles were designed. In this publication the analysis of the tooth of pinions will be focused. Different load forces will be loaded on the top of the tooth on the surfaces of the face cones. The normal stresses and normal deformations of one tooth will be analysed into two perpendicular directions on both tooth sides. The aim is the foundation of the correlation between the mechanical parameters and the shaft angles by the different load forces.